Evaluation of Risk Factors for Retinopathy of Prematurity in Preterm Neonates - Maryam Khosnoud Shariati; Minoo Fallahi; Naeeme Taslimi Taleghani; Mitra Zonubi; Afsar Dastijani Farahani (Mashhad University of Medical Sciences, 2019)
Background: The most common cause of preventable blindness in children is retinopathy of prematurity (ROP). The most important risk factors for this disease are preterm delivery and low birth weight (LBW). This research was performed to evaluate the prevalence ofand risk factors for ROP in preterm neonates. Methods: Our research was a cross-sectional descriptive and retrospective study conducted on preterm neonates in the Neonatal Intensive Care Unit (NICU) of Mahdieh Hospital in Tehran, Iran, in 2015. All neonates with a gestational age of < 32 weeks and birth weight of < 1,500 g were enrolled. Demographic data and risk factors for ROP were evaluated. Statistical analysis was conducted by SPSS (version 20) with a 95% confidence interval and. P-value less than 0.05 was considered statistically significant. Results: Our study was conducted on 154 patients. Mean gestational age and birth weight of the newborns were 28.69±1.82 weeks (range: 23-32 weeks) and 1114.94±240.982 g (range: 550-1500 g). The ROP was detected in 76 (49.4%) patients, 55.26%, 34.2%, and 10.53% of whom had stages I, II, and III of ROP. Stages IV and V were not seen in our patients. The incidence of ROP was significantly affected by low gestational age and birth weight, delivery room resuscitation, prolonged oxygen therapy and mechanical ventilation, and repeated packed cell transfusion. Conclusion: Despite the improvement in the care of preterm infants in the NICUs, the prevalence rate of ROP was high. Therefore, it is critical to adopt better care for disease prevention, timely screening, and appropriate treatment programs for the neonates who are at the risk of this disease.